2016
DOI: 10.2196/jmir.5086
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Behavioral Interventions for Social Media Delivery

Abstract: Patients are increasingly using online social networks (ie, social media) to connect with other patients and health care professionals—a trend called peer-to-peer health care. Because online social networks provide a means for health care professionals to communicate with patients, and for patients to communicate with each other, an opportunity exists to use social media as a modality to deliver behavioral interventions. Social media-delivered behavioral interventions have the potential to reduce the expense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
114
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 56 publications
(79 reference statements)
2
114
0
2
Order By: Relevance
“…First, the research team held regular meetings to review the protocol for the in-person Fresh Start Trial [40] as well as the DPP manual [41]. The team identified key constructs and topics from the sessions and created a library of Facebook posts [22] that were originally copied verbatim from the in-person protocol. In accordance with the Fresh Start protocol, posts emphasized one new topic each week (e.g.…”
Section: Adaptation Processmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the research team held regular meetings to review the protocol for the in-person Fresh Start Trial [40] as well as the DPP manual [41]. The team identified key constructs and topics from the sessions and created a library of Facebook posts [22] that were originally copied verbatim from the in-person protocol. In accordance with the Fresh Start protocol, posts emphasized one new topic each week (e.g.…”
Section: Adaptation Processmentioning
confidence: 99%
“…Language was then simplified and messages were shortened through the use of simple terms, short sentences and other approaches. As research has shown that Facebook engagement is higher when a post has a photo or video [22,42] Step-by-step depiction of adaptation process for Facebook planning to move out of the area within the study period.…”
Section: Adaptation Processmentioning
confidence: 99%
See 3 more Smart Citations